Disseminate Recurrent Folliculitis and Hidradenitis Suppurativa Are Associated Conditions: Results From a Retrospective Study of 131 Patients With Down Syndrome and a Cohort of 12,351 Pediatric Controls - Andrea Sechi; Alba Guglielmo; Annalisa Patrizi; Francesco Savoia; Guido Cocchi; Miriam Leuzzi; Marco A. Chessa; Annalucia Virdi; Iria Neri (Mattioli1885, 2019)
Background: Hidradenitis suppurativa (HS) is a chronic, inflammatory, recurrent skin disease of the pilosebaceous unit characterized by protean manifestations. Several studies have found an increased incidence and earlier presentation of this disease in patients carrying trisomy 21. Patients with Down syndrome (DS) have a higher risk of developing a wide range of cutaneous manifestations, including HS and chronic folliculitis. Recently, disseminate recurrent folliculitis (DRF) has been reported as an atypical monosymptomatic feature of HS at its onset. Objective: To assess the prevalence of HS and DRF by comparing a cohort of patients carrying trisomy 21 vs pediatric controls. Methods: A retrospective 2-year monocentric clinical study was performed by collecting clinical data of 131 patients with DS, aged 4-36 years, followed at the Dermatology Unit and Down Syndrome Regional Center of Bologna University. Data were matched with those coming from 12,351 pediatric controls. Results: In DS patients, DRF and HS showed a prevalence of, respectively, 6.8% and 24.4%, while 5.3% of patients presented both diseases. In the control group the prevalence for HS+ and DRF+ was 0.5% and 1.2%, respectively, with a 0.14% of overlap cases. The association between HS and DRF proved to be statistically significant in both groups (P < 0.05). In the DS cohort the mean age of symptoms onset was 15.67 (SD: 2.29) years for HS and 13.11 (SD: 4.93) years for DRF. Buttocks were the most frequently affected body area for DRF followed by the inguinocrural area, while in HS buttocks were less frequently involved than groins and upper thighs. Conclusions: Because of the later onset of HS, patients with DRF at an early age should be monitored for the possible onset of HS in the apocrine-bearing areas.